Analysis of the impact of sports sponsorship by Banco Panamericano: an event study - Márcio Mellaci (FUCAPE Business School, 2012)
This work provides evidence of the impact of decisions by companies to invest in publicity on soccer jerseys and the reflection of such investments on their stock price, based on the efficient market hypothesis (Fama, 1970). Employing the event study method, we carried out an exploratory study of the performance of the preferred shares of Banco Panamericano (BPNM4), which are listed on the BM&FBovespa. The event analyzed is the announcement on April 23, 2009 of an agreement to sponsor the Corinthians professional soccer team in the last games of the São Paulo state championship competition that year. We investigated the abnormal returns of the bank’s preferred shares based on the model of Campbel, Lo & Mackinlay (1997). After calculating the normal and abnormal returns, we tested the homogeneity of the variances and normality of the data before applying parametric t-tests. Upon validation, we carried out tests of the means for the abnormal returns within the event window, before and after the announcement. The results provide support for the semi-strong market efficiency hypothesis, since the shares presented abnormal performance in the days after disclosure of the sponsorship.